1995
DOI: 10.4206/bosque.1995.v16n1-07
|View full text |Cite
|
Sign up to set email alerts
|

Nutrientes minerales y crecimiento de árboles abonados de Eucalyptus grandis en el Estado de São Paulo

Abstract: This paper discusses the relationship between nutrients concentration in the leaves and soil, as well as tree growth in Eucalyptus grandis plantations. The survey was carried out in five locations in the Cerrado region of the State of São Paulo, Brazil. It was concluded that the trees were adequately nourished with S, Fe, Mn and Zn; P concentrations in the leaves were below the optimum reported in literature; K and Mg were the nutrients that most seriously limited tree growth, in ali locations despite fertiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
0
6
0
5
Order By: Relevance
“…Nutrient concentration in leaves is influenced by diverse factors such as site conditions, age, position of leaves and season [34]. Bellote [5], who worked with Eucalyptus grandis in Brazil, observed that nutrient concentration in leaves varies with stand age and the season. The high amount of N in the leaves of Acacia mearnsii is due to the capacity of this species to fix N. In tropical soils Acacia mearnsii is able to fix up to 200 kg N ha -1 yr -1 [2].…”
Section: Resultsmentioning
confidence: 99%
“…Nutrient concentration in leaves is influenced by diverse factors such as site conditions, age, position of leaves and season [34]. Bellote [5], who worked with Eucalyptus grandis in Brazil, observed that nutrient concentration in leaves varies with stand age and the season. The high amount of N in the leaves of Acacia mearnsii is due to the capacity of this species to fix N. In tropical soils Acacia mearnsii is able to fix up to 200 kg N ha -1 yr -1 [2].…”
Section: Resultsmentioning
confidence: 99%
“…To assess nutrient content in trees during sampling, an age of three years old must be chosen since at this age E. grandis shows larger biomass accumulation per time unit. This is due to three-year-old trees' bigger capacity to absorb soil nutrients and according to Bellote (1990) to the fact that nutrient content in three-year-old E. grandis mature leaves shows the highest values.…”
Section: Resultsmentioning
confidence: 92%
“…Nutrient concentration in leaves is influenced by diverse factors such as site conditions, age, position of leaves and season (Van der Driessche 1984). Bellote (1990) observed that nutrient concentration in leaves of Eucalyptus grandis in Brazil varies with stand age and with the season. If E. camaldulensis canopy concentrates 54.7% of total aboveground biomass nutrients, an exploitation system that preserves these tree components in the site would mean that approx.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Em oposição aos altos teores dos micronutrientes encontrados nas folhas, verificou-se que os menores teores foram localizados no componente madeira. A concentração de nutrientes das folhas das árvores é influenciada por diversos fatores, como a idade das árvores, a estação do ano (VAN DER DRIESSCHE, 1984;BELLOTE, 1990), as condições do sítio e a posição em que as folhas estão dispostas na copa (VAN DER DRIESSCHE, 1984).…”
Section: Teor De Micronutrientes Nos Componentes Arbóreosunclassified